Investing in community: conceptualizing inclusive school design for America's Arctic. (1st October 2016) - Herrmann, Victoria
ABSTRACT: Alaska is going through a major demographic shift. With lower infant mortality rates and better geriatric treatment, Alaskan society's youngest and oldest sectors are quickly becoming its largest. The exchange of traditions and knowledge between generations is fundamental to the well-being of any community, and is exceptionally important for the Alaskan Native population. However, channeling youth into schools and expecting seniors to live in age-homogeneous communities has eroded the social support networks that once connected one generation to the next. This article considers a design solution to Alaska's demographic schism through building schools as community centers. First, the article will position community schools in a wider framework of moving investment in Alaska away from natural resources and into human capital. It will explore a shift in focus to human development in the Arctic and provide a framework based on resiliency for considering future investments. It will then argue for designing school infrastructure as community centers that are sensitive to native culture and the Arctic landscape, support traditional knowledge exchange, recognize the causes of high dropout rates, and are inclusive of all members of the community, with special attention at connecting elders to students. The paper will include case studies of linking policy with school design and community building, and include a discussion of their co-benefits.